Real-Time Optimally Adapting Meshes: Terrain Visualization in Games. (14th January 2008) - White, Matthew
Abstract : One of the main challenges encountered by interactive graphics programmers involves presenting high-quality scenes while retaining real-time frame rates on the hardware. To achieve this, level-of-detail techniques can be employed to provide a form of control over scene quality versus performance. Several algorithms exist that allow such control, including the real-time optimally adapting mesh (ROAM) algorithm specifically aimed at terrain systems. Although ROAM provides an excellent approach to terrain visualization, it contains elements that can be difficult to implement within a game system. This paper hopes to discuss these factors and provide a more game-orientated implementation of the algorithm.